Pengaruh Kematangan Pegawai, Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Pekerjaan Umum Dan Penata Ruang - Mianto Junardi Pardosi; Riwansyah; Rizki Fauzan; Ismail Pahmi Rangkuti; Mawaddah Pardede; Supar Wasesa; M. Nelson Pinem (ARBITRASE: Journal of Economics and Accounting, 2023)
Problem of this study is how influence of employees maturity on employee’s performance. How influence of organization culture on employee’s performance. How influence job dicipline on employee’s performance. How influence of employees maturity, organization culture and job dicipline on employee’s performance. The purpose of this study to determine and analyze the effect of employees maturity on employee’s performance. Determine and analyze the effect of organization culture on employee’s performance. Determine and analyze the effect of job dicipline on employee’s performance. Determine and analyze the effect of employees maturity, organization culture and job dicipline on employee’s performance. Sample in the study is 54 employee’s. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate employees maturity variable has a positive and significant effect on employee’s performance. Organization culture variable has a positive and significant effect on employee’s performance.  Job dicipline variable has a positive and significant effect on employee’s performance. Employees maturity, organization culture and job dicipline variable’s has a positive and significant effect on employee’s performance